Encephalitis with radial perivascular emphasis: Not necessarily associated with GFAP antibodies. Issue 2 (March 2020) - Wickel, Jonathan; Chung, Ha-Yeun; Kirchhof, Klaus; Boeckler, David; Merkelbach, Stefan; Kuzman, Peter; Mueller, Wolf C.; Geis, Christian; Günther, Albrecht
Abstract : Objective: Autoimmune steroid-responsive meningoencephalomyelitis with linear perivascular gadolinium enhancement in brain MRI is regarded as glial fibrillary acidic protein (GFAP) astrocytopathy characterized by anti-GFAP antibodies (ABs). We questioned whether anti-GFAP ABs are necessarily associated with this syndrome. Methods: Two patients with a strikingly similar disease course suggestive of autoimmune GFAP astrocytopathy are reported. Clinical examination, MRI, laboratory, and CSF analysis were performed. Neuropathologic examination of brain tissue was obtained from one patient. Serum and CSF were additionally tested using mouse brain slices, microglia-astrocyte cocultures, and a GFAP-specific cell-based assay. Results: Both patients presented with subacute influenza-like symptoms and developed severe neurocognitive and neurologic deficits and impaired consciousness. MRIs of both patients revealed radial perivascular gadolinium enhancement extending from the lateral ventricles to the white matter suggestive of autoimmune GFAP astrocytopathy. Both patients responded well to high doses of methylprednisolone. Only one patient had anti-GFAP ABs with a typical staining pattern of astrocytes, whereas serum and CSF of the other patient were negative and showed neither reactivity to brain tissue nor to vital or permeabilized astrocytes. Neuropathologic examination of the anti-GFAP AB-negative patient revealed infiltration of macrophages and T cells around blood vessels and activation of microglia without obvious features of clasmatodendrosis. Conclusions: The GFAP-AB negative patient had both a striking (para)clinical similarity and an immediate response to immunotherapy. This supports the hypothesis that the clinical spectrum of steroid-responsive meningoencephalomyelitis suggestive of autoimmune GFAP astrocytopathy may be broader and may comprise also seronegative cases.